Hak dan Kewajiban Penjual dan Pembeli dalam kesepakatan Perjanjian Jual Beli Secara Lisan Menurut Hukum Perdata - Mahara Saputri, Dea (Pamulang Law Review, 2024)
Buying and selling is a common form of transaction that is often carried out by people. Usually, a sale and purchase agreement is made verbally or in writing based on the agreement of the parties (seller and buyer). Talking about buying and selling transactions, it cannot be separated from the basic concept of agreement as contained in Article 1313 of the Civil Code which confirms that an agreement is an act by which one or more people bind themselves to one or more other people. The provisions governing agreements are contained in Book III of the Civil Code, which has an open nature, meaning that its provisions can be set aside, so that they only function to regulate. The open nature of the Civil Code is reflected in Article 1338 paragraph (1) of the Civil Code which contains the principle of Freedom of Contract, meaning that every person is free to determine the form, type and content of the agreement. The agreement does not conflict with applicable laws and regulations, decency and submission in general. Therefore, every legal act, whether written or unwritten, must contain an element of justice for the parties entering into an agreement which will give rise to an agreement.